Assassin's witness [large type] - Colt, Paul (Colt, Paul. Great Western Detective League, 2022)
"Two powerful railroads clash in a dispute over the Royal Gorge right-of-way to serve a valuable silver strike in Colorado. A reclusive financier with substantial holdings in the Denver & Rio Grande commissions the Knights of Labor to foment labor unrest against rival Atkins Topeka & Southern to delay development of the Royal Gorge spur while the dispute is litigated. Stephen Atkins, owner of the AT&S, turns to Pinkerton for assistance in breaking the strike. Atkins learns financier Eli Chorus is responsible for his labor troubles. He calls on Don Victor Carnicero and his El Anillo crime syndicate to eliminate his Chorus problem. When Great Western Detective League operative Beau Longstreet breaks up the assassination attempt, killing the El Anillo assassin, he becomes the assassin's witness. Don Victor vows vengeance. El Anillo operatives threaten Longstreet's life and the life of his love. Assassin's Witness careens from violent confrontation to diabolical treachery in a deadly hail of bullets shrouded in mystery and tainted in loss"--